A robust large-pore zirconium carboxylate metal–organic framework for energy-efficient water-sorption-driven refrigeration. (November 2018) - Wang, Sujing; Lee, Ji; Wahiduzzaman, Mohammad; Park, Jaedeuk; Muschi, Mégane; Martineau-Corcos, Charlotte; Tissot, Antoine; Cho, Kyung; Marrot, Jérôme; Shepard, William; Maurin, Guillaume; Chang, Jong-San; et al.
Abstract The discovery of more-efficient and stable water adsorbents for adsorption-driven chillers for cooling applications remains a challenge due to the low working capacity of water sorption, high regeneration temperature, low energy efficiency under given operating conditions and the toxicity risk of harmful working fluids for the state-of-the-art sorbents. Here we report the water-sorption properties of a porous zirconium carboxylate metal–organic framework, MIP-200, which features S-shaped sorption isotherms, a high water uptake of 0.39 g g−1 below P/P0 = 0.25, facile regeneration and stable cycling, and most importantly a notably high coefficient of performance of 0.78 for refrigeration at a low driving temperature (below 70 °C). A joint computational–experimental approach supports that MIP-200 may be a practical alternative to the current commercially available adsorbents for refrigeration when its water adsorption performance is combined with advantages such as the exceptional chemical and mechanical stability and the scalable synthesis that involves simple, cheap and green chemicals. Porous metal–organic frameworks (MOFs) can be used as sorbents in water-adsorption-driven chillers, but are currently limited in terms of stability and efficiency. Here the authors present a chemically and mechanically stable zirconium carboxylate MOF with a high coefficient of performance for refrigeration.